PERSEPSI KONSUMEN TERHADAP PRODUK PRIVATE LABEL INDOMARET ( STUDI PADA INDOMARET BANJARMASIN KELURAHAN BENUA ANYAR) - Nurul Hasanah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The results of this study Consumers prefer private label products because consumers believe that prices are relatively cheap and have good quality. seen from the interview table that the price of private label products is cheaper. Apart from the price, the quality of private label products in Indomaret Banjarmasin is the same quality as the national brand product. In the packaging of private label products slightly less attractive than the national brand products, while for the value of the function for private label products can be an alternative choice to substitute the national brand products. From the Rating Scale rating Private label products are located at